A survey of placement and follow-up methods used in the employment of the vocationally handicapped in northeastern Colorado - Morton, Joseph V., author; Comstock, George A., advisor; Heilig, Herb, committee member; McClanahan, Walter R., committee member; Morgan, David H., committee member; Samuelson, Cecil O., committee member (Colorado State University. Libraries, 1947)
To view the abstract, please see the full text of the document.
Keywords: People with disabilities; Vocational rehabilitation